Multi-Sensor based Human Activity Recognition - Mehta, Ruchita; Palade, Vasile; Sharifzadeh, Sara (Zenodo, 2025)
Dataset Description Multi-sensor data collection has been done in June,2021 at Coventry University. In this data collection, three types of sensors (Radar, InfraRed and Acoustic) were fused together by a MATLAB code. There were one sensor for radar and acoustic sensors each and  three IR (Grid-Eye) sensors were integrated together to eliminate limitation of a single sensor and to get maximum benefit of Multi-Sensor Human Activity Detection. Overall, 11 subjects took part in the data-collection process which were mainly post graduate researched and academics. Collected dataset is novelty in itself as in this experiment, a series of human activities were performed rather than performing a single activity each time. The experiment was designed carefully by keeping elderly people in the mind. Each series comprise of some day-to-day activities such as walking, sitting, talking and so on. It also has some situation which need attention such as fall, asking for help and so on. In this data collection, seven set of activities were recorded among which series one to three were single subject and series four to seven were dual subject activities. Each series was performed ten times by each subject.  Each series of activities were performed ten times by each subject. Description of each series is given below. Series Number of Subject Activity Series-1 Single Sit(talking)+SitTostanding(help)+walking(leftToright)(caughing)+falling(screaming) Series-2 Single Bending (Pickup Food) +walk (Right to Left) (coughing)+stand to sit(talking)+sit while eating Series-3 Single walking corner left diagonally to corner right (drop a metal spoon) +return (diagonally +help) +bending to take the spoon(talk)+standing from Bending(scream)+walking to the original corner (drop the spoon)